Faktor – faktor yang berhu Usia Pertama Berhubungan Sek Pada Wanita Usia Subur (WUS) Di Provinsi Banten (Analisis Data Sekunder SDKI 2017) - Aminah Mu'min (Akademi Kebidanan La Tansa Mashiro, 2021)
Women of Reproductive Age are a nation's asset, because future generations will be born who will lead the world. However, this also has a risk if the first age of having sex in women of childbearing age (wus) is done too early. Because the reproductive organs are immature which will result in negative effects on health.The age at first having sex in women of childbearing age is influenced by various factors, which will be explained in this study. This study aims to determine whether there is a relationship between education level, area of residence and wealth quintals.This research study is a quantitative analysis, using secondary data from the 2017 SDKI Banten Province. The focus of this study was all women of childbearing age, whether married or not, aged 15-49 years, totaling 1722 people. The independent variables in this study are: education level, area of residence and wealth quintals. While the dependent variable is the age at which you first had sex.From the results of the study it was found that the age at first having sex at the highest age was 16 years as much as 66.7% and the least was at the age of 16-20 years as much as 6.2%. The highest education was high school graduates at 55.1% and the least was PT education at 13.4%.The most residential areas are in cities as much as 74.3% and the least in villages as much as 25.7%. the highest quintal of wealth is in the top category as much as 35.4% and the smallest is in the lowest position as much as 9.3%. From the results of the bivariate analysis, it was found that the p value = .000 for the variable level of education, area of residence and quintal of wealth, which means that all variables have a significant relationship to the age at first having sex in women of childbearing age. The conclusion obtained in this study is that the level of education must be increased, so that WUS have broad knowledge and can determine their attitude from the knowledge they have. The area of residence should not prevent WUS from obtaining any information, because now even in villages they can access information via the internet. The internet can also be used to improve the economy while still living in the village, so that the quintal of wealth at WUS can increase and they can have economic independence.